Pengaruh Implementasi Metode Outdoor Study Terhadap Hasil Belajar Pendidikan Agama Kristen Dan Budi Pekerti Peserta Didik Kelas X Semester Ganjil SMA Negeri 1 Tampahan Tahun Pembelajaran 2023/2024 - Bella D.O Lumbantoruan; Hasudungan Simatupang; Andrianus Nababan; Frainskoy Rio Naibaho; Baginda Sitompul (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
This research aims to determine the positive and significant influence of the implementation of the outdoor study method on the learning outcomes of Christian religious education and character education for class X odd semester students at SMA Negeri 1 Tampahan for the 2023/2024 academic year. The hypothesis of this research is that there is a positive and significant influence from the implementation of the outdoor study method on the learning outcomes of Christian religious education and character education for class X odd semester students at SMA Negeri 1 Tampahan for the 2023/2024 academic year. This research uses quantitative research methods with descriptive statistics. The population of this study was 40 people so it is called population research. The instruments in this research were a closed questionnaire for variable X and a multiple choice written test for variable Y. There is a positive and significant influence of the implementation of the outdoor study method on the learning outcomes of Christian religious education and character education for class X odd semester students at SMA Negeri 1 Tampahan for the 2023/2024 academic year, namely rcount > rtable (0463>0.312), tcount > ttable (3.220 > 2.021), Y ̂=